Medication Adherence, Barriers to Adherence and Treatment Satisfaction with Antiretroviral Therapy Among Adolescents Living with HIV in Lagos, Nigeria - Oluwole EO; Ibidapo DO; Akintan PE; Adegoke AB; Shogbamimu YO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2023)
Background: The advent of antiretroviral therapy (ART) in controlling Human Immunodeficiency Virus (HIV) disease has been quite effective in ensuring that infected people can enjoy healthy, long, and productive lives. Medication adherence is an essential part of patient care, especially among patients with HIV, as it greatly determines the effectiveness of treatment. Few studies have explored factors influencing medication adherence and treatment satisfaction among adults, with little focus on adolescents. Objectives: To assess medication adherence, treatment satisfaction and factors influencing adherence to ART medication among adolescents living with HIV in Lagos, Nigeria. Methods: This descriptive, cross-sectional study was conducted among diagnosed and registered adolescents aged 10-19 years living with HIV and receiving treatment at eight selected antiretroviral centres in Lagos state, Nigeria. A total of 203 adolescents were recruited in stages, and data were collected using an interviewer-administered semi-structured questionnaire. Results: There was a low level of adherence as only 59/203 (29.1%) of the respondents adhered to ART. Depression, perceived stigma, being away from home, side effects of drugs, pill burden, and forgetfulness were some factors identified as barriers to adherence. The respondents were most satisfied with the effectiveness of the medication and least satisfied with the side effects. Conclusions: Medication adherence among adolescents was relatively low; the level of satisfaction with ART medication is an entity that significantly impacts adherence.